1964
DOI: 10.1063/1.1713272
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Oxide Layers on Gold and Nickel Films Observed by Electron Microscopy

Abstract: Thin films of vapor-deposited nickel and gold, supported only by copper grids, were annealed inside the electron microscope. The microstructures were recorded as a function of temperature. The originally continuous thin films of nickel (150 Å thick) and gold (400 Å thick) form discontinuous islands at temperatures of 700° and 600°C, respectively. The islands of metal are supported by a thin amorphous membrane, in the nickel films identified as NiO, that accounts for the high tensile strengths observed on thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…8,9 In addition, Chao et al 10 reported the formation of NiO on the surface and development of porosity in the Au when thin Ni/Au metallization layers were annealed in oxidizing ambients from 250 to 400°C. Gimpl et al 12 reported agglomeration in gold and nickel, and formation of holes was reported by Jaeger et al 13 in silver films prepared under ultrahigh vacuum conditions followed by exposure to air. Gimpl et al 12 reported agglomeration in gold and nickel, and formation of holes was reported by Jaeger et al 13 in silver films prepared under ultrahigh vacuum conditions followed by exposure to air.…”
Section: Discussionmentioning
confidence: 73%
“…8,9 In addition, Chao et al 10 reported the formation of NiO on the surface and development of porosity in the Au when thin Ni/Au metallization layers were annealed in oxidizing ambients from 250 to 400°C. Gimpl et al 12 reported agglomeration in gold and nickel, and formation of holes was reported by Jaeger et al 13 in silver films prepared under ultrahigh vacuum conditions followed by exposure to air. Gimpl et al 12 reported agglomeration in gold and nickel, and formation of holes was reported by Jaeger et al 13 in silver films prepared under ultrahigh vacuum conditions followed by exposure to air.…”
Section: Discussionmentioning
confidence: 73%
“…The fact that these replicas show better cont,rast compared to replicas of unannealed thin films indicates that the irregularities resulting from annealing (4 stick out more on the thin film surface than the few initial irregularities. The results of thickness measurements of these thin films are in keeping with this picture (Table 1).…”
Section: Experimcntal Resultsmentioning
confidence: 97%
“…As an indication of this may be considered the observed influence [3] of the substrate temperature T, during evaporation of thin films on the magnitude of surface irregularities. An additional support for this assumption can be deduced from the investigations on nickel thin films [4] where some important changes in the structure of those films were observed as well as crystalline growth. There is reason to belicve that such a phenomenon I.…”
Section: Introductionmentioning
confidence: 88%
“…The study of grain boundary grooves at the surface of polycrystalline thin films is of vital importance, and especially in nanomaterial sciences applied to electric and electronic processes. Many studies on thin polycrystalline films showed that when these films are submitted to a sufficient thermal treatment, several holes can be formed conducting to the degradation of materials [1][2][3][4][5][6][7][8][9]. The failure of the films resulted from the formation of grain boundary grooves [9].…”
Section: Introductionmentioning
confidence: 99%